2021
DOI: 10.3390/atmos12050628
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Low-Level Wind Shear Characteristics over Chinese Mainland

Abstract: The characteristics of low-level wind shear (LLWS) over the Chinese mainland were investigated using reports from pilots, air traffic controllers and the number of arriving/departing flights from 2016 to 2020. A preliminary analysis of the impact of the flights on the LLWS reports was carried out, and the cause of LLWS was also investigated. LLWS reports from most airports indicate that LLWS is most likely to occur within 600 m AGL with a higher density below 300 m, but with some exceptions, as wind shear is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In recent years, thanks to advancements in monitoring technology and forecasting capabilities, aviation accidents caused by weather-related factors have seen a significant reduction [37]. However, incidents involving aircraft unable to perform normal takeoffs and landings due to wind shear remain alarmingly common [83][84][85][86][87][88], and one significant cause of wind shear is a microburst. Dry microbursts, in particular, are challenging to detect and pose greater dangers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, thanks to advancements in monitoring technology and forecasting capabilities, aviation accidents caused by weather-related factors have seen a significant reduction [37]. However, incidents involving aircraft unable to perform normal takeoffs and landings due to wind shear remain alarmingly common [83][84][85][86][87][88], and one significant cause of wind shear is a microburst. Dry microbursts, in particular, are challenging to detect and pose greater dangers.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, radar analysis results proved that the cause of LLWS at airports was strong convective clouds that come with an MBA. Several studies at several major Asian airports also found convective clouds to be the dominant trigger factor of LLWS [7], [24]. Such convective clouds are usually accompanied by gust front and MBA [6], [12].…”
Section: The Causes Of Llwsmentioning
confidence: 99%
“…In particular, convective rainfall is often accompanied by thunderstorms, strong winds, and strong windshear, with the characteristics of high intensity, fast change, and intermittent occurrence. According to the fast development of air transportation, it has become urgent to improve the detection and recognition ability of windshear in clean air as well as on rainy days to ensure aircraft safety and efficiency [2].…”
Section: Introductionmentioning
confidence: 99%